Implementasi Algoritma First Come First Served pada Aplikasi Pengelolaan Pendapatan Sewa Fasilitas Olahraga Dispora Kota Palembang - Ayu Diya Silfiani; Muhammad Aris Ganiardi; Mardiana . (KERNEL: Jurnal Riset Inovasi Bidang Informatika dan Pendidikan Informatika, 2026)
Dinas Pemuda dan Olahraga (Dispora) of Palembang City is a government agency responsible for managing public sports facilities. The existing manual management process relying on physical ledgers and direct counter visits frequently causes overlapping booking schedules, inaccurate revenue recording, and the absence of real-time monitoring for management. This study develops a web-based application for sports facility rental and revenue management at Dispora Palembang, implementing the First come first served (FCFS) algorithm as the scheduling queue mechanism and the Rational Unified Process (RUP) as the system development method. FCFS assigns facility slots based on the booking request timestamp (Arrival Time), ensuring fair and conflict-free scheduling. A simulation with five tenant scenarios produced an Average Turnaround Time (ATAT) of 120 minutes and an Average Waiting Time (AWT) of 12 minutes, demonstrating that FCFS effectively handles queue conflicts arising from competing bookings on the same facility. The system was built using React.js, MySQL, and Apache. Blackbox  Testing across 21 test scenarios covering all major functions yielded a 100% pass rate. The developed system successfully digitized the complete facility rental workflow: user registration and verification, real-time facility availability checking, FCFS-based booking with database lock, payment upload and admin verification, automatic ticket and confirmation dispatch, and automated periodic revenue reporting for management.